2001
DOI: 10.1002/jcp.1102
|View full text |Cite
|
Sign up to set email alerts
|

Calyculin‐A induces focal adhesion assembly and tyrosine phosphorylation of p125Fak, p130Cas, and paxillin in Swiss 3T3 cells

Abstract: Treatment of intact Swiss 3T3 cells with calyculin-A, an inhibitor of myosin light chain (MLC) phosphatase, induces tyrosine phosphorylation of p125(Fak) in a sharply concentration- and time-dependent manner. Maximal stimulation was 4.2 +/- 2.1-fold (n = 14). The stimulatory effect of calyculin-A was observed at low nanomolar concentrations (<10 nM); at higher concentrations (>10 nM) tyrosine phosphorylation of p125(Fak) was strikingly decreased. Calyculin-A induced tyrosine phosphorylation of p125(Fak) throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 73 publications
(90 reference statements)
1
29
0
Order By: Relevance
“…Inhibition of mTOR suppresses phosphorylation of the focal adhesion proteins A close relationship between F-actin reorganization and tyrosine phosphorylation of focal adhesion proteins has been described (Leventhal et al, 1997;Guvakova and Surmacz, 1999;Leopoldt et al, 2001). As IGF-I stimulation very quickly induced F-actin reorganization, next we examined whether IGF-I impacts tyrosine phosphorylation of the focal adhesion proteins in Rh1 and Rh30 cells.…”
Section: Resultsmentioning
confidence: 89%
“…Inhibition of mTOR suppresses phosphorylation of the focal adhesion proteins A close relationship between F-actin reorganization and tyrosine phosphorylation of focal adhesion proteins has been described (Leventhal et al, 1997;Guvakova and Surmacz, 1999;Leopoldt et al, 2001). As IGF-I stimulation very quickly induced F-actin reorganization, next we examined whether IGF-I impacts tyrosine phosphorylation of the focal adhesion proteins in Rh1 and Rh30 cells.…”
Section: Resultsmentioning
confidence: 89%
“…Active ROCK inhibits myosin light chain phosphatase (Kimura et al, 1996), thus causing the stimulation of actomyosin contractility. In turn, application of local forces by actomyosin contractility stimulates FA and stress fiber formation (Chrzanowska-Wodnicka and Burridge, 1996;Leopoldt et al, 2001), whereas inhibitors of actomyosin contractility induce disruption of these structures (Volberg et al, 1994;Helfman et al, 1999;Zamir et al, 1999;). Growth of FAs and focal complexes can also be 975 Tyrosine phosphorylation of focal adhesion components is involved in the regulation of focal adhesion formation and turnover, yet the underlying molecular mechanisms are still poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, we observed that class I-induced activation of the PI3K/Akt cell survival pathway and fibroblast growth factor (FGF) receptor (FGFR) expression was inhibited by cytochalasin D and latrunculin A, suggesting that FAK regulates both class I-mediated activation of the PI3K/Akt survival pathway and cell proliferation (10). However, much of what we conjecture about FAK interactions with effectors in the class I signal transduction pathway is based upon the pharmacological inhibitors cytochalasin D and latrunculin A that prevent actin polymerization (20). This approach, although informative, is limited by the challenges inherent in establishing the specificity of these agents.…”
mentioning
confidence: 99%